PENGARUH MEDIASI BUDAYA ORGANISASI DALAM HUBUNGAN PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMITMEN ORGANISASI DENGAN KINERJA ORGANISASI - Arini Novandalina (Jurnal Ilmiah Infokam, 2014)
This research test influence mediation organization culture in relationship participation of composing a budget and organization commitment with organization performance.Samples of this research is teachers SMA City in Semarang, with a quota sampling. The method of analysis used to test a questionnaire is reliabilitas and validity test. While technique regression analysis using mediation, by fit model appropriateness and test assumption classic.The result showed that only participation of composing a budget and commitment of the organization that influential positive significantly affect the organizations cultural, and organization cultural significant positive influence on the performance of the organization. While the participation of composing a budget and commitment of the organization no significant positive on the performance of the organization. But organization cultural it is proven as variable mediation relations participation of composing a budget and commitment of the organization with the performance of the organization.Keywords : Cultural mediation, budget preparation, organinizational preparation.1. PENDAHULUAN